PERDAGANGAN INFORMAL PELINTAS BATAS DI KABUPATEN MALINAU DAN SERAWAK MALAYSIA - Syachrumsyah Asri; Muhammad Nizar Hidayat (Jurnal Paradigma (JP), 2017)
This research discloses and describes how cross-border trade and its implications for improving people's welfare in Malinau district of East Kalimantan, especially in border villages. The factors behind the cross-border trade are: topographical and geographical factors, accessibility factors, cost and price factors, and cultural background and emotional relations. The pattern of trade that developed in recent years is no longer in the pattern of direct barter alone but has developed into direct trading patterns. The results show that the results of the development process still tend to be urban bias and less to reach areas that are far from the "center of power". The results also reinforce the viewpoint that development is a "chain of imbalances" which means it will create a dependent pattern among the "minus" groups of the "surplus" group.Keywords: trade, border, Malinau, basic needs.